2019
DOI: 10.14203/treubia.v45i0.3706
|View full text |Cite
|
Sign up to set email alerts
|

Notes on ecology of wild goffin’s cockatoo in the late dry season with emphasis on feeding ecology

Abstract: Experimental work on captive Goffin’s cockatoos (Cacatua goffiniana) has highlighted the remarkable cognitive abilities of this species. However, little is known about its behavior in the natural habitat on the Tanimbar Archipelago in Indonesia. In order to fully understand the evolutionary roots leading to cognitively advanced skills, such as multi-step problem solving or flexible tool use and manufacture, it is crucial to study the ecological challenges faced by the respective species in the wild. The three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…In their natural habitat, the small Tanimbar archipelago in the Moluccan region of Indonesia, the Goffin’s cockatoos feed on wild maracuja ( Passiflora foetida ; Mioduszewska et al, 2019 ; O’Hara et al, 2019 ). These flowering plants produce small individual fruit pods growing on long vines and represent a highly valuable foraging source to the wild cockatoos.…”
Section: Discussionmentioning
confidence: 99%
“…In their natural habitat, the small Tanimbar archipelago in the Moluccan region of Indonesia, the Goffin’s cockatoos feed on wild maracuja ( Passiflora foetida ; Mioduszewska et al, 2019 ; O’Hara et al, 2019 ). These flowering plants produce small individual fruit pods growing on long vines and represent a highly valuable foraging source to the wild cockatoos.…”
Section: Discussionmentioning
confidence: 99%
“…Like in the crows, the products made by the birds in the Size test should be regarded as assimilations based on the memorized models and not as absolute matches of the latter (with exceptions; see above). Finding the ability to physically produce object features of a template in a parrot that has the capacity for tool innovation (Auersperg et al 2012 ; Osuna-Mascaró and Auersperg 2018 , Laumer et al 2017 ) but, so far, seems to lack a dependency on tool use and does not have cumulative tool cultures (O’Hara et al 2018 ; Mioduszewska et al 2019 ) suggests that the latter is not a necessary condition in order for this ability to evolve. We suggest it is likely that crows and parrots may share other inherent properties that facilitate such skills.…”
Section: Discussionmentioning
confidence: 99%
“…Cacactua goffiniana is the only cockatoo species endemic to Tanimbar Islands. This bird [17]. In this study, we often observed that while these bird species can establish a nest on the same tree, they might use different parts.…”
Section: Association Between C Goffiniana and Other Birds On Tanimbar Islandsmentioning
confidence: 95%